Adaptive Platform Trials to Transform Amyotrophic Lateral Sclerosis Therapy Development. Issue 2 (10th January 2022) - Paganoni, Sabrina; Berry, James D.; Quintana, Melanie; Macklin, Eric; Saville, Benjamin R.; Detry, Michelle A.; Chase, Marianne; Sherman, Alexander V.; Yu, Hong; Drake, Kristin; Andrews, Jinsy; Shefner, Jeremy; et al.
Abstract : Current therapeutic development in amyotrophic lateral sclerosis (ALS) relies on individual randomized clinical trials to test a specific investigational product in a single patient population. This approach has intrinsic limitations, including cost, time, and lack of flexibility. Adaptive platform trials represent a novel approach to investigate several interventions for a single disease in a continuous manner. Already in use in oncology, this approach is now being employed more often in neurology. Here, we describe a newly launched platform trial for ALS. The Healey ALS Platform Trial is testing multiple investigational products concurrently in people with ALS, with the goal of rapidly identifying novel treatments, biomarkers, and trial endpoints. ANN NEUROL 2022;91:165–175